Effect of para (p) Position Methoxy Group on The Synthesis of Benzohydrazide Derivatives from Methylbenzoate Starting Material - Suzana, Suzana; Ardhayanti, Erlina; Amalia Novianti, Kholis; Ekowati, Juni; Budiati, Tutuk (Universitas Airlangga, 2022)
The synthesis of N'-benzylidenebenzohydrazide and N'-(4-methoxybenzylidene)benzohydrazide was performed through a condensation reaction. The reaction was performed in two stages with methylbenzoate as the initial material. In the first phase, benzohydrazide was obtained by reacting methylbenzoate and hydrazine hydrate; in the second phase, the compounds N'-benzylidenebenzohydrazide and N'-(4- methoxybenzylidene)benzohydrazide were obtained by reacting benzohydrazide and benzaldehyde/4- methoxybenzaldehyde. The results obtained were 87% and 92%, respectively. A purity test was done by thin layer chromatography (TLC) and melting point determination. The melting point of benzohydrazide was 108-111°C, N'-benzylidenebenzohydrazide had a melting point of 104-108°C, and N'-(4- methoxybenzylidene)benzohydrazide had a melting point of 159-161°C. The synthesized compounds were identified by UV-VIS, FT-IR, and 1H-NMR spectroscopy. Keywords: Synthesis, N' -benzylidenebenzohydrazide, N’- (4-methoxybenzylidene)benzohydrazide, methylbenzoate